2011
DOI: 10.4172/2155-9627.1000109
|View full text |Cite
|
Sign up to set email alerts
|

Case-Report: Autonomy and Self Determination of an Elderly Population in South Brazil

Abstract: Some elderly members of a small community in the state of Rio Grande do Sul, Brazil were victims of fraudulent behavior by a group of criminals. It happened shortly before the development of a research project that evaluated quality of life and decision-making capacity. Such a crime was a significant trauma for the victims and, as a result, the participants of the research refused to sign the Informed Consent Form. This case serves as background for supporting the distinction -sometimes confused in the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
2
0
1
Order By: Relevance
“…The results of our sample showed that all the patients' decision-making abilities were preserved, which is consistent with other studies involving vulnerable populations, such as older adults, research participants, and adoles-cents (37,40,41,45,47,48). This is also consistent with other studies which have shown that the moral-psychological development of individuals is not impacted by age and educational level(41).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The results of our sample showed that all the patients' decision-making abilities were preserved, which is consistent with other studies involving vulnerable populations, such as older adults, research participants, and adoles-cents (37,40,41,45,47,48). This is also consistent with other studies which have shown that the moral-psychological development of individuals is not impacted by age and educational level(41).…”
Section: Resultssupporting
confidence: 91%
“…In a case report based on a study of the elderly population of a municipality located in the state of Rio Grande do Sul, Bajotto and Goldim(47) demonstrated this distinction between autonomy and self-determination. Many of the elderly were deemed capable according to the administration of an assessment tool of moral-psychological development; however, in practice their ability to make autonomous decisions was impeded by other family members who took control of the decision-making process (47).…”
Section: Resultsmentioning
confidence: 99%
“…In a study that sought to differentiate autonomy of selfdetermination, the authors from this paper, took as a starting point a community of seniors who had been temporarily discouraged to act without the consent of family to differentiate the concept of autonomy and self-determination. While the former refers to the ability to make decisions, the second term refers to the ability to put the decision into practice, denotes "action [21]".…”
Section: Discussionmentioning
confidence: 99%
“…A garantia do respeito à autodeterminaçãopoder expressar seus desejos e participar ativamente do planejamento dos seus cuidados de saúde -vem sendo progressivamente incorporada à prática dos profissionais da área 4 . É importante diferenciar autonomia, entendida como capacidade de decidir, e autodeterminação, como exercício de decisão 5 .…”
unclassified